Antibodi monoklonal terhadap antigen protein 36 kd dari Mycobacterium leprae dan aplikasinya dalam serodiagnosis lepra - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1991)
ABSTRAk Identification of M. leprae antigens and development of monoclonal antibodies CO those antigens have brought about progress in the serodiagnosis of leprosy and have partly overcome the limitations of clinical, bacteriological dan histopathological diagnosis. Thirty six kD protein antigen of M. leprae contains a specific epitope of M. leprae which is recognized both by monoclonal antibody and by T-cells. Elisa Inhibition is a serological test using the monoclonal antibody to the 36 kD protein of M. leprae antigen. In Indonesian populations, this test shows high sensitivity (98.1% for multibacilaty and 81.8% for paucibacilary leprosy) with 92% specificity. Compared to the ocher serological tests, using monoclonal antibody in the test has resulted in higher sensitivity and specificity. Because of the high sensitivity for both paucibacilary and multibaciltary leprosy, it is suggested that the.epiu3p on 36 kI) protein of M. leprae antigen is immunodominant. This paper describes preparation of antigen and monoclonal antibody, and the Elisa Inhibition test, and application in serodiagnosis of leprosy and infection ofM leprae.